Anger as a moral emotion: A "bird's eye" systematic review. Issue 3 (2nd October 2019) - Lomas, Tim
ABSTRACT: Anger is a common problem for which counselling and psychotherapy clients seek help, and is typically regarded as an invidious negative emotion to be ameliorated. However, in some instances it may be possible to reframe anger as a moral emotion, arising in response to perceived transgressions, thereby endowing it with meaning. In that respect, this paper offers a "bird's eye" systematic review of empirical research on anger as a moral emotion (i.e., focusing broadly on the terrain as a whole, rather than on specific areas). Three databases were reviewed from the start of their records to February 2019. Eligibility criteria included empirical research, published in English in peer-reviewed journals, on anger specifically as a moral emotion. A total of 175 papers met the criteria, and fell into four broad classes of study: survey-based; experimental; physiological; and qualitative. In discussing the articles, this paper looks at: how anger can be differentiated from other moral emotions; antecedent causes and triggers of moral anger; contextual factors that influence or mitigate it; and outcomes arising from it. Together, the paper offers a comprehensive overview of current knowledge of this prominent and problematic emotion. The results may be of use to counsellors and psychotherapists helping to address anger issues in their clients.